Reduction of material handling in an automobile assembly line through lean manufacturing - Huerta Estévez, Antonio (2021)
This article focuses on the application of lean manufacturing principles to an automobile assembly plant, which had production line stoppages and long runs that generated losses caused by failure to deliver the units on time to dealers. In the end, line stoppages were reduced by up to 50% that generated savings of $383,751.